Secure Data Management with Blockchain-Enabled Attribute Based Access Control (International Journal of Innovative Research in Engineering & Management, 2023)
The security of computerized systems  depends on mechanisms for controlling access. For the  enrichment and reinforcement of such systems, a  combination of attribute-based access control and  blockchain technologies may be deployed. On the other  hand, attribute-based encryption may be used to enable  secure data management and safeguard access policies. In  this research, we have presented innovative blockchain enabled attribute-based access control. Our architecture is  the first to integrate different aspects to accomplish many  security aspects as well as give partial and total revocation  at the same time. The experimental findings and analysis,  done utilizing the blockchain of the Ethereum network,  proved the superior performance of the suggested method  compared to prior research works.
Keywords: Block chain; Attribute; revocation; tree; smart contract; access policies